1998
DOI: 10.1093/carcin/19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of estrogen metabolism in target cells: review and perspectives

Abstract: Cytochrome P450 enzymes that metabolize estrogens are expressed in the mammary gland, uterus, brain and other target tissues for estrogen action, and this results in the formation of hydroxylated estrogens in these tissues. Estradiol metabolites formed in target tissues at or near estrogen receptors may either be inactive or have important biological effects, and changes in the activities of estrogen-metabolizing enzymes in target tissues may profoundly influence estrogen action. Although some active estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
778
1
11

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 850 publications
(814 citation statements)
references
References 415 publications
15
778
1
11
Order By: Relevance
“…CYP1A2 is considered as one of the most important enzymes in the 2-hydroxylation of estrogens, 3 and accumulating evidence indicates an association between CYP1A2*1F and breast cancer risk. 14,[30][31][32][33] Findings have been inconsistent, however, showing no association for Chinese, 30 Caucasian 31 or American-African women; 31 a positive association for Russian women; 33 and an inverse association for a multiethnic group (Multiethnic Cohort Study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP1A2 is considered as one of the most important enzymes in the 2-hydroxylation of estrogens, 3 and accumulating evidence indicates an association between CYP1A2*1F and breast cancer risk. 14,[30][31][32][33] Findings have been inconsistent, however, showing no association for Chinese, 30 Caucasian 31 or American-African women; 31 a positive association for Russian women; 33 and an inverse association for a multiethnic group (Multiethnic Cohort Study).…”
Section: Discussionmentioning
confidence: 99%
“…1 An association between circulating levels of estrogen metabolites and risk has also been hypothesized, on the basis that these are potentially both estrogenic and genotoxic. 2,3 In particular, the association between the urinary ratio of 2-hydroxy (2-OHEs) to 16a-hydroxy estrogens (16a-OHEs) and breast cancer risk has been extensively examined, [4][5][6][7][8] whereas many studies have also investigated associations between single nucleotide polymorphisms (SNPs) related to estrogen metabolism and risk. 2 Although many branch pathways in estrogen metabolism have been demonstrated after hydroxylation, the biological properties of the metabolites are determined mainly by the position of the hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this expectation, it has been shown that O-methylation results in a faster clearance rate than sulfation or glucuronidation and that 2-methoxyestrone (produced by COMT-mediated O-methylation of estrogen) is one of the most abundant estrogen metabolites in plasma and urine. 45 It should be noted that 2-methoxyestrone is a very potent inhibitor of tumor cell proliferation, 46 indicating the dual anti-cancer function of COMT in actively suppressing tumor growth and in passively preventing mutation. Although the genes involved in the CE-metabolizing pathway as a whole contributed significantly to preventing breast cancer formation, our findings also suggest that the anti-oxidation effect of MnSOD and the CE-Q-inactivating conjugation reactions (mediated by GST genes) are not as important as the detoxification reaction mediated by COMT.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogenic hormones are catabolized to hormonally inactive (or less active) water-soluble metabolites that are excreted in the urine and/or feces. The metabolic elimination of estrogens relies on oxidative metabolism (largely hydroxylations by cytochromes P450 enzymes (Zhu and Conney, 1998) and conjugations by glucuronidation (Barbier and Bélanger, 2003), sulfonation (Song, 2001;Song and Melner, 2000) and/or O-methylation (Männistö and Kaakkola, 1999). While hydroxylated products retain some estrogenic activity, conjugations appear to markedly decrease hormonal activity.…”
Section: Cellular Mechanisms: In Vivo Clearance Of Estrogensmentioning
confidence: 99%
“…High levels of 2-and 4-hydroxylases have, for example, been identified in the brain, notably the preoptic-hypothalamic region, in various species including quail (Balthazart, Stoop, Foidart, Granneman, and Lambert, 1994;Lambert and van Oordt, 1982;Timmers, Granneman, Lambert, and van Oordt, 1988;Zhu and Conney, 1998). The 2-and 4-hydroxyestrogens (also called catecholestrogens) are biologically active compounds but they are rapidly metabolized by the catecholamine-O-methyltransferases (COMT) into methoxyestrogens that have a weaker hormonal activity (Männistö and Kaakkola, 1999).…”
Section: Cellular Mechanisms: In Vivo Clearance Of Estrogensmentioning
confidence: 99%